2015
DOI: 10.1371/journal.pone.0121005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Restraint Stress, Prolonged Captivity Stress and Transdermal Corticosterone Application on Immunocompetence and Plasma Levels of Corticosterone on the Cururu Toad (Rhinella icterica)

Abstract: Glucocorticoid steroids modulate immunocompetence in complex ways with both immunoenhancing and immunosuppressive effects in vertebrates exposed to different stressors. Such bimodal effects have been associated with variation in duration and intensity of the stress response. Given that natural populations have been exposed to a multitude of stressors, a better understanding of the functional association between duration and intensity of the stress response, the resulting changes in glucocorticoid plasma levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
105
1
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 70 publications
(86 reference statements)
10
105
1
4
Order By: Relevance
“…To distinguish among these hypotheses, more measures of immune function and determining health outcomes of animals with particular immune profiles are necessary to understand whether the immune system is primed or suppressed in association with elevated plasma CORT. For example, after immobilization restraint, cururu toads had decreased bacterial killing ability along with increased plasma CORT and decreased percentage lymphocytes in the blood, suggesting suppression of immune function (de Assis et al, 2015). Study of additional immune factors would also indicate whether the relationships between HPA/I activity and white blood cell count differentials extend to other measures of innate or cell-mediated immunity.…”
Section: No Relationship Of Hpa/i Activity With Reproductive Investmentmentioning
confidence: 99%
“…To distinguish among these hypotheses, more measures of immune function and determining health outcomes of animals with particular immune profiles are necessary to understand whether the immune system is primed or suppressed in association with elevated plasma CORT. For example, after immobilization restraint, cururu toads had decreased bacterial killing ability along with increased plasma CORT and decreased percentage lymphocytes in the blood, suggesting suppression of immune function (de Assis et al, 2015). Study of additional immune factors would also indicate whether the relationships between HPA/I activity and white blood cell count differentials extend to other measures of innate or cell-mediated immunity.…”
Section: No Relationship Of Hpa/i Activity With Reproductive Investmentmentioning
confidence: 99%
“…These studies suggest that, although chronically elevated plasma CORT and/ or T appear to be immunosuppressive, this is not necessarily the case of acute CORT elevation (Martin 2009) and, furthermore, that T may interact with the effects of CORT. However, few studies of wild animals have investigated interactions between plasma CORT and innate immune performance during acute stress (Berger et al 2005;de Assis et al 2015;Graham et al 2012;Merrill et al 2012;Seddon and Klukowski 2012), and, to our knowledge, none has investigated the simultaneous responses of CORT, T, and innate immune performance in a wild vertebrate. Considering that plasma CORT and T change rapidly during the stress response, it is unclear which, if any, of these hormones is correlated with the changes in immune function during acute stress in wild animals.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using a restraint stress protocol in birds showed a reduction in BKA and a negative correlation with CORT . In anuran amphibians, studies using a restraint stress protocol and long-term captivity (Assis et al, 2015) reported declines in BKA, but there were no significant correlations between CORT and BKA in any of them. In the present study, there were no correlation between BKA and CORT (except for a positive correlation in R. ornata, after the restraint with movement restriction), and the decrease in BKA on R. icterica was expected and supported by aforementioned studies.…”
Section: Intraspecific Effectsmentioning
confidence: 86%
“…Animals under chronic stress usually show higher baseline levels (Assis et al, 2015) and a lower increase in CORT when submitted to acute stress (Gadek-Michalska and Bugajski, 2003;Love et al, 2003). This attenuation of the stress response with chronic stress has been alternativelty interpreted as habituation (the perception or cognitive interpretation of the stressors), exhaustion (the state in which the animal can no longer compensate for sustained stress and effects become life-threatening), or downregulation (the mechanism that alters CORT release could be a function of the adrenal tissue itself, through downregulation of ACTH receptors or a decreased ability to manufacture the steroids) .…”
Section: Interspecific Comparisonsmentioning
confidence: 99%